2017
DOI: 10.1071/sh16067
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccination in men who have sex with men – what will be required by 2020 for the same dramatic changes seen in heterosexuals

Abstract: Abstract. This paper addresses the issue of whether men who have sex with men (MSM) will share the spectacular reductions in human papillomavirus (HPV) infection and its associated neoplasia that we are currently witnessing in heterosexuals. The reproductive rate for HPV infection in heterosexuals is not well established, but 70% vaccination coverage in women has resulted in a fall of more than 90% in genital warts and HPV types 16/18 in young women and 80% fall in young men indicating that the critical vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Similar reductions have also been observed among unvaccinated heterosexual men due to herd protection 4 5 26. In order to observe a similar reduction in MSM, it is hypothesised that the vaccine coverage in MSM would need to reach at least 70%, which effectively protects 91% of partnerships (100% (30% by 30%)) 27. Furthermore, an Australian-based mathematical model has predicted that implementing both school-based vaccination programme for boys and a targeted programme for MSM aged up to 26 years would be highly cost-effective 10.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reductions have also been observed among unvaccinated heterosexual men due to herd protection 4 5 26. In order to observe a similar reduction in MSM, it is hypothesised that the vaccine coverage in MSM would need to reach at least 70%, which effectively protects 91% of partnerships (100% (30% by 30%)) 27. Furthermore, an Australian-based mathematical model has predicted that implementing both school-based vaccination programme for boys and a targeted programme for MSM aged up to 26 years would be highly cost-effective 10.…”
Section: Discussionmentioning
confidence: 99%
“…Since the reproductive rate of HPV infection in MSM is much greater than heterosexual men, it is likely that a higher level of vaccination coverage will be required. 53 Despite only 16 of 26 studies in heterosexual men demonstrating cost effectiveness, our data suggest that a gender neutral vaccination strategy may become increasingly costeffective for a number of reasons. First, recent literatures reported that 1-or 2-doses vaccination is as effective as 3doses vaccination for people age 9-14 years, which means a potential 30% cost reduction per head if this is implemented in any school age vaccination programs.…”
Section: Discussionmentioning
confidence: 79%
“…15 Yet, among these predictions, there is some good news, with considerable decline in human papillomavirus (HPV) infection and associated cancers likely in countries where HPV vaccination coverage exceeds critical vaccination thresholds. 16 However, declines are likely only in countries where childhood vaccination of boys has been implemented, because HPV is so rapidly acquired after commencing sexual activity that vaccination of GBM after sexual debut will have much less impact. 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…16 However, declines are likely only in countries where childhood vaccination of boys has been implemented, because HPV is so rapidly acquired after commencing sexual activity that vaccination of GBM after sexual debut will have much less impact. 16,17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation